2022
DOI: 10.1002/ejoc.202200677
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Oxidation of Glucose in Glycopeptides**

Abstract: Selective modification of carbohydrate residues in glycopeptides is highly relevant as a tool in glycobiology. In particular, oxidation allows for subsequent ligation with a label or handle and can be effectuated enzymatically or chemically. Chemical oxidation of carbohydrate residues in glycopeptides is nearly invariably done using periodate cleavage, leading to aldehydes. In this work, we applied palladium-catalyzed oxidation for the same purpose. The catalyst, [(neocuproine)PdOAc] 2 OTf 2 , developed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We propose that steric interactions between the bulky L 3 ligand and glycoside substrates may overcome intrinsic electronic factors that favor oxidation at C3 . The dependence of chemoselectivity on the ligand structure observed here therefore offers an opportunity to obtain rare oxidized glycosides, which can undergo further functionalization to yield valuable carbohydrate products. , …”
Section: Resultsmentioning
confidence: 86%
“…We propose that steric interactions between the bulky L 3 ligand and glycoside substrates may overcome intrinsic electronic factors that favor oxidation at C3 . The dependence of chemoselectivity on the ligand structure observed here therefore offers an opportunity to obtain rare oxidized glycosides, which can undergo further functionalization to yield valuable carbohydrate products. , …”
Section: Resultsmentioning
confidence: 86%
“…The problems associated with catalyst inhibition can occasionally be overcome by using the palladium catalyst in excess, often in combination with excess ligand. [2,4,7,31] Under these conditions, the catalyst concentration in solution will be sufficient to perform the reaction, even when most of the catalyst forms non-productive complexes with the Lewis basic groups in the substrate (Figure 1D). High catalyst loadings are standard for palladium-mediated cross-coupling reactions on proteins, [7] and have also been used to promote other palladium-catalyzed reactions that suffer from catalyst inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to the commonly used strategies, the field of regioselective modification of unprotected carbohydrates is growing rapidly [23–25] . In this connection, the groups of Minnaard and Waymouth have shown that the C‐3 hydroxy group in pyranosides can be selectively oxidized with a palladium catalyst to afford the corresponding 3‐ketosaccharide [26–29] . Further modification and derivatization have also been done on these unprotected ketosaccharides [30–32] …”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] In this connection, the groups of Minnaard and Waymouth have shown that the C-3 hydroxy group in pyranosides can be selectively oxidized with a palladium catalyst to afford the corresponding 3-ketosaccharide. [26][27][28][29] Further modification and derivatization have also been done on these unprotected ketosaccharides. [30][31][32] Here, we show how the C3-keto functionality in unprotected carbohydrates can be used to introduce an allyl group, which in turn is transformed into a fused methylene-tetrahydrofuran ring (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%